Some identities from the q-binomial transform - Wang, Weiping; Liu, Hongmei (Utilitas Mathematica, 2012)
In this paper, by using the properties of the q-generalized Seidel matrix, we establish general identities involving the sequence (a n) nεN and its q-binomial transform (b n) nεN. As applications, various identities are deduced, especially some related to the q-dual sequences, the qBernoulli polynomials and the q-Stirling numbers of the second kind. It can be found that many known results are special cases of ours.